Experimental and simulation approach of cooling system in 3-phase inverter using extended surface - Agus Mukhlisin; Prisma Megantoro; Estiko Rijanto; I Nyoman Sutantra; Lilik Jamilatul Awalin; Yoga Uta Nugraha; Indra Sidharta (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Overheating is a failure mode that significantly affects the reliability of electronic devices. All electronic devices, including a 3-phase inverter driving a traction motor, produce heat dissipation. Heat dissipation needs to be controlled with cooling to prevent overheating. Overheating can be avoided by increasing cooling or reducing heat dissipation. Heat dissipation in the 3-phase inverter is caused by the internal resistance of the metal–oxide–semiconductor field-effect transistor (MOSFET), switching loss, and other factors. Cooling for the 3-phase inverter can use water coolant or air coolant. The cooling system is based on the amount of heat dissipation produced. Cooling of a 3-phase inverter can use air coolant with the addition of an extended surface area in the heat sink. The heat sink uses aluminum material, often called pin fin. There are kinds of aluminum available in the market. We calculated heat generation based on the MOSFET's internal resistance, switching loss, and other factors. We validated the simulation results experimentally using a thermal camera. Thus, we could find an optimal number, dimensions, and aluminum type of fin for the cooling system in the 3-phase inverter.